Controlling the Chromaticity of Small‐Molecule Light‐Emitting Electrochemical Cells Based on TIPS‐Pentacene. (14th July 2015) - Weber, Michael D.; Adam, Matthias; Tykwinski, Rik R.; Costa, Rubén D.
Abstract : This work demonstrates a novel proof‐of‐concept to implement pentacene derivatives as emitters for the third generation of light‐emitting electrochemical cells based on small‐molecules (SM‐LECs). Here, a straightforward procedure is shown to control the chromaticity of pentacene‐based lighting devices by means of a photoinduced cycloaddition process of the 6, 13‐bis(triisopropylsilylethynyl) (TIPS)‐pentacene that leads to the formation of anthracene‐core dimeric species featuring a high‐energy emission. Without using the procedure, SM‐LECs featuring deep‐red emission with Commission Internationale d'Eclairage (CIE) coordinates of x = 0.69/ y = 0.31 and irradiance of 0.4 μW cm −2 are achieved. After a careful optimization of the cycloaddition process, warm white devices with CIE coordinates of x = 0.36/ y = 0.38 and luminances of 10 cd m −2 are realized. Here, the mechanism of the device is explained as a host–guest system, in which the dimeric species acts as the high‐energy band gap host and the low‐energy bandgap TIPS‐pentacene is the guest. To the best of the knowledge, this work shows the first warm white SM‐LECs. Since this work is based on the archetypal TIPS‐pentacene and the photoinduced cycloaddition process is well‐knownfor any pentacenes, this proof‐of‐concept could open a new way to use these compounds for developing white lighting sources. Abstract : TIPS‐pentacene has been tested as an emitter in small‐molecule light‐emitting electrochemical cells (SM‐LECs). The formation of high‐energy band gap species via photoinduced cycloaddition process has been exploited to control the device chromaticity from red to white. As such, this work provides a proof‐of‐concept that opens a new avenue to fabricate white lighting sources based on pentacene derivatives.